Reflections on the Rega Institute for Medical Research, at the fiftieth anniversary of the Rega Stichting vzw (Rega Instituut vzw, Rega Foundation). (October 2022) - Clercq, Erik De
The idea to start the Rega Foundation was conceived in 1971 at an informal meeting organized by Prof. Piet De Somer (where Prof. Alfons Billiau, Prof. André Vlerick and I were also present), before the Foundation was formally created in 1972. From the early years some antiviral compounds, such as BVDU and the aminoacyl esters of acyclovir (from which ultimately valacyclovir evolved) originated. The advent of AIDS in 1981 and the discovery of the etiologic agent (HIV) thereof in 1983 have led to the identification of an avalanche of anti-HIV compounds in which the Rega Institute has played a primordial role. Foremost among these compounds was tenofovir, discovered in collaboration with Antonín Holý from the IOCB (Institute of Organic Chemistry and Biochemistry) in Prague. Tenofovir laid the basis for the treatment of HIV (AIDS) and hepatitis B virus (HBV) infections, and in combination with emtricitabine it was the first chemical ever approved by the US FDA (Food and Drug Administration) for the prophylaxis of HIV infections.